Optimising co-design with ethnic minority consumers - Ashfaq Chauhan (BMC, 2021)
Abstract Co-design as a participatory method aims to improve health service design and implementation. It is being used more frequently by researchers and practitioners in various health and social care settings. Co-design has the potential for achieving positive outcomes for the end users involved in the process; however, involvement of diverse ethnic minority population in the process remains limited. While the need to engage with diverse voices is identified, there is less information available on how to achieve meaningful engagement with these groups. Ethnic minorities are super-diverse population and the diversity between and within these groups need consideration for optimising their participation in co-design. Based on our experience of working with diverse ethnic minority groups towards the co-design of consumer engagement strategies to improve patient safety in cancer services as part of the two nationally-funded research projects in Australia, we outline reflections and practical techniques to optimise co-design with people from diverse ethnic backgrounds. We identify three key aspects of the co-design process pertinent to the involvement of this population; 1) starting at the pre-commencement stage to ensure diverse, seldom heard consumers are invited to and included in co-design work, 2) considering logistics and adequate resources to provide appropriate support to address needs before, during and beyond the co-design process, and 3) supporting and enabling a diversity of contributions via the co-design process.